The Incidence of Akathisia in the Treatment of Schizophrenia with Aripiprazole, Asenapine and Lurasidone: A Meta-Analysis - E. Thomas, Jennifer; Caballero, Joshua; A. Harrington, Catherine (Current Neuropharmacology, 2015)
Akathisia is a troubling side effect that leads to non-adherence with antipsychotic regimens. Second generation antipsychotics (SGAs) tend to cause less akathisia than older agents but the risk still exists and rates vary between agents. Little is known about the incidence of akathisia among the newer SGAs. The purpose of this study was to conduct a meta-analysis of akathisia incidence rates for three of the newer SGAs: aripiprazole, asenapine, and lurasidone. Data were drawn from published and unpublished clinical trials comparing the drug of interest to either placebo or another SGA in adults with schizophrenia. Twenty-four studies (11 aripiprazole, 5 asenapine, and 8 lurasidone) provided incidence rates for akathisia and related nervous system events. Data showed that the relative risk (RR) of akathisia was double that of controls, with lurasidone having the highest individual RR at 2.7 [CI: 2-3.6]. Sensitivity analysis changed the RR of akathisia to less than 10%. The RR of akathisia was still elevated (1.75 [1.4-2.1]) when these drugs were compared only to actives (older SGAs). Agitation and anxiety RRs were also higher with the newer SGAs as compared to the older SGAs. Previous theory suggests antagonism of serotonin (5-HT)2A receptors may decrease akathisia risk. Expectations were that aripiprazole, asenapine and lurasidone would have a low incidence of akathisia, as all display strong antagonism at 5-HT2A. However, in this study all three had a significantly higher risk of akathisia compared to placebo or other SGAs. This suggests the pathophysiology of akathisia involves other receptors and is multifactorial.
Keywords: aripiprazole